Programmed death-1/programmed death-L1 signaling pathway and its blockade in hepatitis C virus immunotherapy - Salem, Mohamed L (World J Hepatol, 2015)
Chronic hepatitis C virus (HCV) infection is a public health issue that often progresses to life-threatening complications, including liver cirrhosis, fibrosis, and hepatocellular carcinoma. Impaired immune responses to HCV are key features of chronic HCV infection. Therefore, intervention strategies usually involve enhancing the immune responses against HCV. Cytotoxic CD8(+) T lymphocytes (CTLs) play a critical role in the control of HCV infection. However, their cytolytic function can be impaired by the expression of co-inhibitory molecules. Programmed death-1 (PD-1) receptor and its ligand PD-L1 function in a T cell co-inhibitory pathway, which either blocks the function of CTLs or the differentiation of CD8(+) T cells. During chronic HCV infection, the immune inhibitory receptor PD-1 is upregulated on dysfunctional HCV-specific CD8(+) T cells. As such, blockade of the PD-1/PD-L1 pathway in these CD8(+) T cells might restore their functional capabilities. Indeed, clinical trials using therapies to block this pathway have shown promise in the fostering of anti-HCV immunity. Understanding how chronic HCV infection induces upregulation of PD-1 on HCV specific T cells and how the PD-1/PD-L1 interaction develops HCV specific T cell dysfunction will accelerate the development of an efficacious prophylactic and therapeutic vaccination against chronic HCV infections, which will significantly improve HCV treatments and patient survival. In this review, we discuss the relationship between PD-1 expression and clinical responses and the potential use of PD-1 blockade for anti-HCV therapy.